Leaf morphoanatomy of rheophyte Dyckia distachya Hassler (Bromeliaceae) - Heinig Voltolini, Caroline; Reis, Ademir; Santos, Marisa (Revista Brasileira de Biociências, 2009)
This research reports on the leaf morphoanatomy of the rheophyte Dyckia distachya. Plants with young and mature leaves of three populations from the Pelotas River and Uruguay River (SC, Brazil), which were maintained in a greenhouse, were utilized in the study. The leaves of D. distachya have sheaths, and the blades are lanceolate with serrate margins. The leaf epidermis of this species has a thickened cuticular membrane; thickened and lignified cellular walls, except in the outer periclinal; and silica bodies in the lumen. Tetracytic stomata are found within individual depressions that are protected by peltate scales; both the stomata and scales are restricted to the intercostal zones, on the abaxial surface. These features of the epidermis suggest that this species has the ability to conserve water while gas is exchanged during periods when the water level is low. The mesophyll is formed by the following: the hypodermis, which is made of septate fibers (along the adaxial surface and abaxial costal regions) or sclereids (abaxial intercostal regions); hydrenchyma, the widest tissue; chlorenchyma, located adaxially to the collateral vascular bundles; and aerenchyma, which communicate directly with the stomata. The leaf sheath has neither scales nor stomata. Dyckia distachya has both xeromorphic and hydromorphic features, which are associated with survival during periods when the water level is low or is high, respectively.